2018
DOI: 10.1002/er.3967
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salinity concentration on algal biomass production and nutrient removal from municipal wastewater by Dunaliella salina

Abstract: Summary Extensive amounts of organic and inorganic substances are discharged into the environment, and they have been ascribed to a number of anthropogenic activities including agriculture, industry, and domestic processes. Microalgae, as a promising alternative feedstock for bioenergy production, have advantages in the uptake of nutrients from wastewater for biomass production. This study assessed the feasibility of mass cultivation of microalgae in controlled environment tertiary treated municipal wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Among all combinations studied, optimal algal growth was observed at 30 ppt salinity level, with a 75% wastewater concentration (3:1 ratio of wastewater and saline water mixture, which is the growth medium). These findings concluded that D. salina has great capacity for nutrient uptake while providing high-value bioproducts [60].…”
Section: Dunaliella Salinamentioning
confidence: 82%
See 1 more Smart Citation
“…Among all combinations studied, optimal algal growth was observed at 30 ppt salinity level, with a 75% wastewater concentration (3:1 ratio of wastewater and saline water mixture, which is the growth medium). These findings concluded that D. salina has great capacity for nutrient uptake while providing high-value bioproducts [60].…”
Section: Dunaliella Salinamentioning
confidence: 82%
“…A very recent study assessed the feasibility of the cultivation of D. salina in controlled environment tertiary-treated municipal wastewater [60]. D. salina was selected for its high β-carotene generation capacity and for being a halophilic species to protect our fresh water resources further through wastewater remediation.…”
Section: Dunaliella Salinamentioning
confidence: 99%
“…The optimal salinity for D. salina found in this study is higher compared with other studies on both D. salina and other Dunaliella species. When cultivated at 0.5 mol L −1 NaCl salinity mixed with municipal wastewater, D. salina showed the highest biomass production . For Dunaliella sp.…”
Section: Resultsmentioning
confidence: 99%
“…When cultivated at 0.5 mol L −1 NaCl salinity mixed with municipal wastewater, D. salina showed the highest biomass production. 33 For Dunaliella sp. isolated from the South China Sea, the optimal salinities for cultivation are 0.5 and 0.9 mol L −1 , while at 0.9 mol L −1 salinity the microalga accumulated the highest protein content of around 50% during the stationary phase.…”
Section: Experiments 2: Effect Of Salinitymentioning
confidence: 99%
“…Mahsa et al have reported that the total biomass and protein concentrations of marine Spirulina platensis were observed under blue light, at around 100 µmol photons m −2 s −1 of 13.4 and 9.0 g L −1 , respectively. However, the highest phosphate and ammonium removal were about 145 and 218 mg L −1 under purple light, at around 100 µmol photons m −2 s −1 , respectively [97]. Results showed that light intensity and wavelength, combined with semi-batch cultivation, can be designed to achieve the highest biomass and production, as well as to maximize the removal of phosphorous and ammonium.…”
Section: Promoted Nitrogen and Phosphorus Removal In Wastewatermentioning
confidence: 99%